SINERGI DIGITALISASI DAN KEBERLANJUTAN: PEMBERDAYAAN UMKM PESISIR DI ERA EKONOMI BIRU - Muh Mappatunru; Andi M. Rusli; Suhardiman Syamsu (ITB Swadharma, 2026)
Digital transformation has become a key driver of competitiveness and sustainability for micro, small, and medium-sized enterprises (MSMEs), particularly in coastal regions where the blue economy is increasingly promoted. However, how digitalization empowers coastal MSMEs while aligning with sustainability principles remains underexplored. This study examines the integration of digitalization and sustainability to empower coastal MSMEs within the blue economy framework, focusing on Luwu Regency, South Sulawesi, Indonesia. Using a qualitative descriptive approach, data were collected through semi-structured in-depth interviews, focus group discussions, and observations involving 20 MSME owners and workers who had adopted or attempted to adopt digital technologies. Thematic analysis was employed to identify adoption levels, enabling and constraining factors, and empowerment strategies. The findings indicate that digital adoption remains partial, largely limited to social media for promotion, while e-commerce use is constrained by low digital literacy, inadequate infrastructure, and cultural resistance. Nevertheless, when integrated with sustainability-oriented practices, digitalization enhances business efficiency, expands market access, and strengthens competitiveness. This study proposes a strategic empowerment model emphasizing digital literacy development, infrastructure improvement, sustainability-based local branding, multi-stakeholder collaboration, and continuous mentoring to support sustainable blue economy development.Transformasi digital menjadi pendorong penting daya saing dan keberlanjutan usaha mikro, kecil, dan menengah (UMKM), khususnya di wilayah pesisir dalam konteks ekonomi biru. Namun, peran digitalisasi dalam memberdayakan UMKM pesisir yang selaras dengan prinsip keberlanjutan masih belum banyak dikaji. Penelitian ini bertujuan menganalisis sinergi digitalisasi dan keberlanjutan dalam pemberdayaan UMKM pesisir di Kabupaten Luwu, Sulawesi Selatan. Penelitian menggunakan desain deskriptif kualitatif dengan pengumpulan data melalui wawancara mendalam, diskusi kelompok terarah, dan observasi terhadap 20 pelaku UMKM yang telah atau sedang mengadopsi teknologi digital. Analisis tematik digunakan untuk mengidentifikasi tingkat adopsi, faktor pendorong dan penghambat, serta strategi pemberdayaan. Hasil penelitian menunjukkan bahwa adopsi digital masih bersifat parsial dan didominasi penggunaan media sosial, sementara e-commerce belum optimal akibat keterbatasan literasi digital, infrastruktur, dan resistensi budaya. Namun, integrasi digitalisasi dengan praktik berkelanjutan terbukti meningkatkan efisiensi usaha, memperluas akses pasar, dan memperkuat daya saing. Penelitian ini mengusulkan model pemberdayaan strategis berbasis literasi digital, penguatan infrastruktur, pengembangan merek lokal berkelanjutan, kolaborasi multipihak, dan pendampingan berkelanjutan untuk mendukung pembangunan ekonomi biru yang berkelanjutan